Decreased expression of vesicular glutamate transporter 1 and complexin II mRNAs in schizophrenia: further evidence for a synaptic pathology affecting glutamate neurons. - Eastwood, S; Harrison, P (2005)
Synaptic protein gene expression is altered in schizophrenia. In the hippocampal formation there may be particular involvement of glutamatergic neurons and their synapses, but overall the profile remains unclear. In this in situ hybridization histochemistry (ISHH) study, we examined four informative synaptic protein transcripts: vesicular glutamate transporter (VGLUT) 1, VGLUT2, complexin I, and complexin II, in dorsolateral prefrontal cortex (DPFC), superior temporal cortex (STC), and hippocampal formation, in 13 subjects with schizophrenia and 18 controls. In these areas, VGLUT1 and complexin II are expressed primarily by excitatory neurons, whereas complexin I is mainly expressed by inhibitory neurons. In schizophrenia, VGLUT1 mRNA was decreased in hippocampal formation and DPFC, complexin II mRNA was reduced in DPFC and STC, and complexin I mRNA decreased in STC. Hippocampal VGLUT1 mRNA declined with age selectively in the schizophrenia group. VGLUT2 mRNA was not quantifiable due to its low level. The data provide additional evidence for a synaptic pathology in schizophrenia, in terms of a reduced expression of three synaptic protein genes. In the hippocampus, the loss of VGLUT1 mRNA supports data indicating that glutamatergic presynaptic deficits are prominent, whereas the pattern of results in temporal and frontal cortex suggests broadly similar changes may affect inhibitory and excitatory neurons. The impairment of synaptic transmission implied by the synaptic protein reductions may contribute to the dysfunction of cortical neural circuits that characterises the disorder.